2017
DOI: 10.21776/ub.jitek.2017.012.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Properties of Collagen of Broiler’s Bone Prepared Under Different Combination Processes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Based on the results of the study, the characteristics of water-soluble collagen products extracted from Alaska Pollock (Theragra chalcogramma) fish skin through a pre-treatment with different concentrations of acetic acid showed that the proximate compositions met the criteria of Indonesian National Standard (SNI 8076:2014). The optimal pre-treatment to produce water-soluble collagen from Alaska Pollock fish skin was using 0.15 M of acetic acid resulting in the highest yield the pH value can affect the viscosity and strength of the collagen gel (Said et al, 2017). The pH value can be affected with the use of acetic acid concentration and neutralization process after soaking with acids or bases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the study, the characteristics of water-soluble collagen products extracted from Alaska Pollock (Theragra chalcogramma) fish skin through a pre-treatment with different concentrations of acetic acid showed that the proximate compositions met the criteria of Indonesian National Standard (SNI 8076:2014). The optimal pre-treatment to produce water-soluble collagen from Alaska Pollock fish skin was using 0.15 M of acetic acid resulting in the highest yield the pH value can affect the viscosity and strength of the collagen gel (Said et al, 2017). The pH value can be affected with the use of acetic acid concentration and neutralization process after soaking with acids or bases.…”
Section: Discussionmentioning
confidence: 99%